Assessing SPECT/CT for the identification of cartilage lesions in the knee joint: A systematic review - Larissa Rix; Samuel Tushingham; Karina Wright; Martyn Snow (Osteoarthritis and Cartilage Open)
Background: Single-photon emission computerised tomography with conventional computer tomography (SPECT/CT) is an emerging technology which may hold clinical value for the identification of cartilage lesions in the knee joint. The intensity and distribution of SPECT/CT uptake tracer may identify physiological and structural information in the absence of structural change on other imaging modalities. Objectives: To systematically assess the utility of SPECT/CT in the detection of chondral lesions within the knee joint, in patients presenting with knee pain, with or without structural change. Results: PubMed, Science Direct, Web of Knowledge, and NHS databases were searched for English language articles focusing on the diagnostic value of SPECT/CT for knee chondral lesions and knee pain. Animal studies, cadaver studies, comparator radiological technique other than SPECT/CT or patients with a pathology other than knee chondral lesions were excluded. From the search, 11,982 manuscripts were identified, and screened for relevance. Seven studies were identified and scored low on QUADAS-2 bias review. SPECT/CT correlated with lesions found on other imaging modalities and during intraoperative assessment. Furthermore, in some cases, SPECT/CT out-performed other modalities in the detection of cartilage lesions. Conclusion: Evidence suggests SPECT/CT may be a useful tool for the detection and localisation of cartilage lesions, particularly in discrepant cases when there is an absence of lesions on other imaging modalities, or a lack of correlation with patients’ symptoms. Further studies are required to confirm the conclusions of this review.